MEDIA DAN KESETARAAN GENDER - jamil Bazarah (Universitas 17 Agustus 1945 Samarinda, 2013)
Essentially, advertising in real is a message that send by communicator to communicant. Advertising as a tool for services or products to be come closer to consumer or target market in real has not have gender perspective. In reality, role of men and women always makes men be higher than women sometimes ‘live’ at advertising.Key words: advertising, gender equalities